2022
DOI: 10.1177/10499091211067811
|View full text |Cite
|
Sign up to set email alerts
|

Early Palliative Care Consults Reduce Patients’ Length of Stay and Overall Hospital Costs

Abstract: Background: Palliative care improves health outcomes and satisfaction and supports decision-making for patients and families during challenging times in their lives. Earlier referral for consults has demonstrated increased costs savings. Hypothesis: Education proposing physicians order a palliative care consult within 3 days of patient hospital admission will decrease patient length of stay (LOS) and overall costs as well as expedite the transition to next level of care. Design/Method: A descriptive retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…At different timepoints before death in the same year, the total length of hospital stay increased as the time of death approached in both enrolled and non-enrolled patients, but the difference between the two groups was not significant, which is inconsistent with the findings of previous studies. For example, studies from the US noted that patients who received hospice and palliative care consultations had shorter hospital stays within 3 months before death than patients who did not [34,35]. Moreover, other studies from the US showed that the longer the length of hospice and palliative care, the greater the reduction in the length of hospital stay [36].…”
Section: Discussionmentioning
confidence: 99%
“…At different timepoints before death in the same year, the total length of hospital stay increased as the time of death approached in both enrolled and non-enrolled patients, but the difference between the two groups was not significant, which is inconsistent with the findings of previous studies. For example, studies from the US noted that patients who received hospice and palliative care consultations had shorter hospital stays within 3 months before death than patients who did not [34,35]. Moreover, other studies from the US showed that the longer the length of hospice and palliative care, the greater the reduction in the length of hospital stay [36].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this brief analysis suggests the need to deepen and, probably, redefine the professional, ethical and clinical role of palliative care teams, not only in the management of COVID patients, but also in the healthcare system as a whole. This also requires a reflection on current clinical-care practices and on how to include an early integration of palliative care team knowledge and expertise at the service of collective and individual health (Zaborowski et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%